Revisiting Interior Water Mass Responses to Surface Forcing Changes and the Subsequent Effects on Overturning in the Southern Ocean - Tesdal, Jan-Erik; MacGilchrist, Graeme A.; Beadling, Rebecca L.; Griffies, Stephen M.; Krasting, John P.; Durack, Paul J. (Zenodo, 2023)
This dataset contains processed model data used in Tesdal, J.-E., A. MacGilchrist, G., Beadling, R. L.,Griffies, S. M., Krasting, J. P., & Durack, P. J. (2023). Revisiting interior water mass responses to surface forcing changes and the subsequent effects on overturning in the Southern Ocean. Journal of Geophysical Research: Oceans, 128, e2022JC019105. https://doi.org/10.1029/2022JC019105 . The above publication uses two coupled climate models (AOGCMs), GFDL-CM4 and GFDL-ESM4, to assess the impact of perturbations in wind stress and Antarctic ice sheet melting on the Southern Ocean meridional overturning circulation (SO MOC) and associated water mass transformations (WMT). The attached archive includes netCDF files to recreate all figures and tables in Tesdal et al. (2023) , including overturning streamfunction (moc), volume storage change (dVdt), surface water mass transformation (swmt), meridional volume transports (mvt) zonal mean potential density referenced to 2000 dbar (sigma2) and mixed layer depth (mld). These variables are derived from preindustrial control (piControl) and idealized perturbation runs of Antarctic melting (Antwater), wind stress (Stress), as well as the combination (Antwater-Stress) using the Flux-Anomaly-Forced Model Intercomparison Project (FAFMIP) protocol. The FAFMIP protocol ( Gregory et al., 2016 ) involves adding perturbations to the surface fluxes that are computed within the atmosphere-ocean general circulation model (AOGCM) from the state of the system ( Lowe and Gregory, 2006 Bouttes and Gregory,2014 ).The perturbations in this dataset were technically added as a flux adjustment similar to that formerly used in AOGCMs ( Sausen et al., 1988 ). The data files contain processed model output and do not include any raw model output.Model data from the piControl runs of CM4 and ESM4 are available at the Earth System Grid Federation archive ( https://esgf-node.llnl.gov/projects/cmip6 ). The forcing fields (perturbations) used in the perturbation experiments can be found at ...